MO251: Renal Glucocorticoid Receptor Expression and Clinical Course in Patients with IGA Nephropathy. (3rd May 2022) - Tekin Ala, Bilge; Paydas, Saime; Kaya, Bülent; Eren Ateş, Kıvılcım; Gönlüşen, Gülfiliz; Sertdemİr, Yaşar
Abstract: BACKGROUND AND AIMS: Glucocorticoids are used as primary treatment in IgA nephropathy (IgAN), and they manifest their effects by binding to intracellular glucocorticoid receptors. Studies have shown that GCR expression correlates with the degree of steroid response in various diseases. Therefore, we aimed to evaluate renal GCR expression, Oxford MEST score in clinical course of IgAN patients. METHOD: This study included 110 patients with biopsy-proven IgAN. Patients were treated with ACEI/ARB, methylprednisolon (80% patients). In renal biopsies, Oxford-MEST score was calculated and GCR expression was determined immunohistochemically. KDIGO criteria (2020) were accepted for remission. Clinical course, eGFR, proteinuria and other biochemical tests test were recorded during 1-year follow-up period. RESULTS: Demographic and laboratory data did not correlate with renal GCR staining rate. İn patients with M1 of the MEST score, GCR staining was more prominent than those with M0. GFR values were higher and proteinuria was lower in patients with T0 compared with patients with T1 and T2 (P < .05 for all) . Patients with E1 had significantly higher systolic blood pressure (BP), increased proteinuria and lower eGFR than patients with E0. Poor prognostic factors for achieving remission were higher systolic/diastolic BP, increased levels of white blood cell (WBC) count/neutrophil count, PTH, BUN, creatinine, uric acid, potassium, magnesium, MCV, Mentzer index, total cholesterol, LDL and higher sclerosis in biopsy at baseline during follow up period for 1 year. CONCLUSION: Clinical presentation and outcome at 1 year in IgAN patients were well predicted by the Oxford-MEST score, but not by renal GCR expression. GCR staining intensity was only correlated with M1 score. Baseline higher BP, increased serum creatinine, uric acid and PTH were poor prognostic factors. Interestingly higher WBC and neutrophils counts, increased serum LDL and Mentzer index at baseline were also correlated with clinical course.